Repeated low impacts in alpine ski helmets - Swaren, M.; Holmberg, H. C.; Eriksson, A. (Sports Technology, 2012)
Alpine ski race helmets are subjected to multiple impacts during a race caused by the skiers hitting the gates on their way down the course. This study investigated the difference between expanded polystyrene (EPS) and expanded polypropylene (EPP) cores in alpine ski race helmets when subjected to repetitive violence, caused by alpine slalom gates. A special test rig was developed where a rotating slalom pole impacted the helmets with a velocity of 13.3 m·s -1. All helmets (six EPS and six EPP) were attached to a headform, monitored with a triaxial accelerometer at the center of mass. Each helmet sustained 1000 impacts and acceleration data were collected around every 200 impacts. No significant differences were observed between the first hit and after 1000 hits for either the EPS or the EPP helmets. However, the total group mean acceleration and mean peak acceleration were 15% and 16% higher, respectively, for the EPS series compared with the EPP series. Also, all EPS helmets showed cracked cores after 1000 impacts compared with 1 cracked EPP core. Findings suggest that EPP cores might be more suitable for absorbing multiple low impacts caused by alpine gates and that repeated violence is a relevant parameter to consider when constructing alpine ski race helmets.